Investigation of the effect of high-fibrous filling material on the mechanical properties of wood plastic composites - Ertuğrul Altuntaş; Esra Yılmaz; Tufan Salan (Turkish Journal of Forestry, 2017)
In this study, wood plastic composite (WPC) materials were produced using high density polyethylene (HDPE) and wood fiber at various ratios ranging from 40% to 70%. The effects of fiber content on mechanical properties such as tensile strength, bending strength, elasticity modulus and shock resistance of these materials were investigated. In addition, maleic anhydride grafted polyethylene (MAPE) was also added to the materials, which had lowest and highest wood fiber additive, to investigate the effect of the binding agent effect. Composite samples were produced via a laboratory type twin screw extruder and test panels were prepared using hot press molding method. According to the results, the bending, tensile and shock resistances generally decreased with the increasing ratio of wood fiber in the composite material content while modulus of elasticity increased for the sample groups without coupling agent. However, the addition of the coupling agent MAPE into the material content significantly improved the mechanical properties. Especially, the addition of MAPE provided better resistance values than all sample groups without MAPE even for the samples containing 70% wood fiber. As a result, with this study, it has been shown that WPC materials with low cost, light weight, aesthetic appearance and good mechanical properties as well could be produced with high fiber ratio.